If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 13 = 35 + -11x Reorder the terms: 13 + 4x = 35 + -11x Solving 13 + 4x = 35 + -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. 13 + 4x + 11x = 35 + -11x + 11x Combine like terms: 4x + 11x = 15x 13 + 15x = 35 + -11x + 11x Combine like terms: -11x + 11x = 0 13 + 15x = 35 + 0 13 + 15x = 35 Add '-13' to each side of the equation. 13 + -13 + 15x = 35 + -13 Combine like terms: 13 + -13 = 0 0 + 15x = 35 + -13 15x = 35 + -13 Combine like terms: 35 + -13 = 22 15x = 22 Divide each side by '15'. x = 1.466666667 Simplifying x = 1.466666667
| 2x-35=43 | | 9m+6=4 | | (-5/3)(1/3)+1/3^3 | | 6=5r-7r | | 16=4n | | 7x^2=30x-8 | | 12t^(2/5)+19t^(1/5)+4=0 | | x/7+45=-60 | | 4(y+5)-6y=2 | | x/7+45= | | 12b+2a=8 | | 3(8x-5)=24 | | 3/8x-1/12=x/3 | | a+5b=19 | | (5/3)(1/3)+1/3^3 | | 12a+2b=8 | | 2x+35=43 | | 15x-8=4x-19 | | 8n+n=9 | | m/-4-3=21 | | -15x(-8)= | | 6(w-6)-8w=-20 | | 4(5x-5)-12= | | 2(3x-1)=7x-3 | | 7+5v+8=-10 | | 5/3*1/3+1/3^3 | | 8n+5=-52+65n | | 4w-12=40 | | 9.2=5.7+h/6+0.6 | | 2/3(1/8+8x)-1/8=7/8 | | -71=64x | | x+4/6=-4 |